2023
DOI: 10.1186/s43556-023-00146-y
|View full text |Cite
|
Sign up to set email alerts
|

Vascular calcification: from the perspective of crosstalk

Shiqi Yang,
Zhaolin Zeng,
Qing Yuan
et al.

Abstract: Vascular calcification (VC) is highly correlated with cardiovascular disease morbidity and mortality, but anti-VC treatment remains an area to be tackled due to the ill-defined molecular mechanisms. Regardless of the type of VC, it does not depend on a single cell but involves multi-cells/organs to form a complex cellular communication network through the vascular microenvironment to participate in the occurrence and development of VC. Therefore, focusing only on the direct effect of pathological factors on va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 320 publications
0
3
0
Order By: Relevance
“…Several studies have identified various factors released from VSMCs in calcification condition, including inflammation, oxidative stress, MMP activity, apoptosis and autophagy, etc 36 . Recently, the discovery of extracellular vesicles secreted during the VC process emphasizes the importance of intercellular/interorgan crosstalks and suggests potentially novel preventive or therapeutic strategies for VC-related diseases 37 . Nevertheless, the specific factors produced in VC contributing to cardiomyocytes apoptosis remain to be determined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified various factors released from VSMCs in calcification condition, including inflammation, oxidative stress, MMP activity, apoptosis and autophagy, etc 36 . Recently, the discovery of extracellular vesicles secreted during the VC process emphasizes the importance of intercellular/interorgan crosstalks and suggests potentially novel preventive or therapeutic strategies for VC-related diseases 37 . Nevertheless, the specific factors produced in VC contributing to cardiomyocytes apoptosis remain to be determined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles released by vascular smooth muscle cells are at the sites of medial vascular calcification [152][153][154][155][156][157][158] and can be involved in atherosclerosis-related vascular calcification [151,159]. Extracellular vesicles can communicate with cells and organs to regulate vascular calcification and may serve as therapeutic methods in vascular calcification [160]. In this respect, it is essential to make a clear distinction between matrix vesicles and media vesicles.…”
Section: Matrix Vesicles and Media Vesicles From Smooth Muscle Cellsmentioning
confidence: 99%
“…Several studies have attempted to identify common underlying pathophysiological processes and their respective mediators in order to explain the established link between CVD and OP [8][9][10][11]. A common feature of both diseases appears to be a low-grade chronic state of inflammation which paradoxically promotes bone formation/calcification of the vasculature [12], but also induces decalcification of hard tissue [13]. The calcification occurs both by deposition of calcium and phosphate on elastin and collagen fibrils in vessels via a passive mechanism independent of cellular activity and also by an active process involving inflammation preceding calcification [13].…”
Section: Introductionmentioning
confidence: 99%